Cardioprotective therapies for ST-elevation myocardial infarction: the emerging role of thyroid hormone: a narrative review - Grigoriou, Konstantinos; Karakasis, Paschalis; Lamprou, Vasileios; Michas, George; Pamporis, Konstantinos; Trikas, Athanasios; Pantos, Constantinos; Mourouzis, Iordanis (Frontiers in Endocrinology, 2025)
The mortality rates and the incidence of cardiac remodeling and subsequent heart failure remain high, despite ongoing advancements in the management of patients with ST-segment elevation myocardial infarction (STEMI). Most of the adjunctive therapies aiming to further reduce myocardial infarction (MI) size have failed to apply in daily clinical practice. In this context, new promising therapeutic approaches aiming to enhance myocardial salvage have emerged. Recent studies have suggested that thyroid hormone (TH) may have regenerative effects on ischemic myocardium. Immediate treatment with TH appears to trigger repair and the regeneration process in the injured myocardium, especially in patients with large infarct sizes. The aim of this narrative review is to summarize the most recent advances in the use of TH for salvaging ischemic myocardium following STEMI and place it among the most promising cardioprotective therapies. Emphasis is placed on preclinical and clinical data that highlight the favorable effects of TH in enhancing myocardial recovery and improving outcomes after acute myocardial ischemia.